Renewed purpose: exploring adaptive reuse for quality, affordable housing in Kansas City, Kansas - Hebbert, Abbey LeAnn (Kansas State University, 2021)
More Americans live in urban areas today than ever before. Factors such as white flight, the relocation of manufacturing overseas, and rural-to-urban migration has resulted in the major shift in where people live. Consequently, cities now are left to grapple with stockpiles of vacant buildings and land. At the same time, the U.S. is facing an acute housing affordability crisis. Inflation is outpacing the growth of household income, the national minimum wage is inadequate in providing means to live from, and the existing federal programs, focused on resolving the affordable housing crisis, are not nearly meeting existing demands. American cities today are therefore, struggling to address both the issue of the proliferation of vacant abandoned buildings as well as to provide affordable, quality housing to all their residents. Kansas City, Kansas is not immune to the housing affordability crisis wreaking havoc across the country and has its own set of issues that need to be resolved. In this report, I explore the application of adaptive reuse for quality, affordable housing in Kansas City, Kansas. In order to provide a holistic perspective to this exploration, I use case studies and semi-structured interviews with representatives from Detroit, Michigan and Rochester, New York. These two sites were chosen for their explicit use of adaptive reuse for affordable housing and adopted or proposed policy on the topic. In order to form a deeper understanding of the issues that KCK faces, I conducted semi-structured interviews with planners, preservationists, and an adaptive reuse developer. The in-depth research and discussions with representatives from each case study location and KCK, are used to present recommendations for future operations within Kansas City pertaining to adaptive reuse for affordable housing. These recommendations include conducting a housing conditions and market study, establishing a team to monitor and report on federally financed developments, pairing historic preservation and affordable housing, adopting explicit policies and zoning ordinances for adaptive reuse, and considering tactical preservation for incremental reuse.
Keywords: Adaptive reuse; Affordable housing; Kansas City, Kansas